1996
DOI: 10.2135/cropsci1996.0011183x003600050006x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Apomictic Reproduction in a Set of 39 Chromosome Maize‐Tripsacum Backcross Hybrids

Abstract: An apomictic form of hybrid maize (Zea mays L.) would provide an immortalized line which would be stabilized against genetic change. The development of agronomically superior, apomictic maize hybrids could provide a superior level of food security in developing nations as well as altering commercial and public maize breeding programs‐systems in developed nations. Backcross selections obtained from an apomictic, 38‐chromosome (20 maize + 18 Tripsacum L.) maize‐Tripsacum hybrid have resulted in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, reduction of Tripsacum chromosome complement was observed in 65% of maize/Tripsacum F1 progeny plants. A previous report (Kindiger et al 1996b) also showed partial loss of Tripsacum chromosomes in backcrosses of an apomictic maize/Tripsacum F1 hybrid (2n = 56).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, reduction of Tripsacum chromosome complement was observed in 65% of maize/Tripsacum F1 progeny plants. A previous report (Kindiger et al 1996b) also showed partial loss of Tripsacum chromosomes in backcrosses of an apomictic maize/Tripsacum F1 hybrid (2n = 56).…”
Section: Resultsmentioning
confidence: 54%
“…Different authors have investigated the possibility to introgress some characteristics from Tripsacum to maize, for example, disease tolerance (Bergquist, 1981), constitutive aerenchyma (Ray et al 1999), and gametophytic apomixis (Leblanc et al 1995b;Kindiger et al 1996b;Lukina and Chistyakova, 1999).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Diplosporous form of apomixis have been identified in some species of Poa (Huff, 1992) and Tripsacum dactyloides (Dewald and Kindiger, 1998). Although there have been several attempts to transfer the apomixis from various wild relatives to the major crops (Kindiger et al ., 1996a; Morgan et al ., 1998), no apomictic commercial cultivars have been released to date.…”
Section: Introductionmentioning
confidence: 99%
“…All 20-chromosome backcross plants derived to date have been annual and non-apomictic. Kindiger et al (1996) derived an annual, 39-chromosome line that carried 9 Tripsacum chromosomes and displayed an intermediate level of apomixis.…”
Section: Hybridization With Eastern Gamagrassmentioning
confidence: 99%
“…The difficulties encountered in introgressing apomixis from Tripsacum into maize (Kindiger et al, 1996) should temper hopes for a rapid synthesis of perenniality with high grain yield. Whatever the initial population, and even with marker-assisted selection, the process of recovering perennial, winterhardy segregants with maize-like ears, and then breeding for yield and other agronomic traits will be long and arduous.…”
Section: Hybridization With Eastern Gamagrassmentioning
confidence: 99%